Analysis of Layered Composite Beam to Underwater Shock Including Structural Damping and Stiffness Effects - S.W. Gong; K.Y. Lam (Shock and Vibration)
This paper deals with the transient response of layered composite beams subjected to underwater shock. The Doubly Asymptotic Approximation (DAA) method is employed in this study to treat the fluid-structure interactions. The effective structural damping and stiffness are formulated and incorporated in the fluid-structure-coupled equations, which relate the structure response to fluid impulsive loading and are solved using coupled finite-element and DAA-boundary element codes. The present computational method facilitates the study of transient response of the layered composite beams to underwater shock, involving the effects of structural damping and stiffness. In addition, the effect of free surface on the transient response of the layered beam to underwater shock is examined.